Closing a distributional gap of over 3000 km and encountering an invisible barrier: new presence/absence data for Johngarthia planata Stimpson, 1860 (Decapoda, Brachyura, Gecarcinidae) for Central America and biogeographic notes on East Pacific Gecarcinidae - Perger, Robert (2013)
Johngarthia planata (Stimpson, 1860) is an abundant and ecologically important land crab, distributed on East Pacific islands from the Gulf of California to Colombia. However, despite possible dispersal of planktotrophic larvae by sea currents, J. planata is not known from inshore islands and mainland of Central America. In this study, the presence of J. planata on Costa Rican inshore islands is reported for the first time, strongly supporting the significance of coastal currents for the distributional patterns of such species. Despite the proximity of the Costa Rican inshore islands to the mainland coast and larval dispersal by passing coastal currents, J. planata was not found in mainland locations. We suggest that a high diversity of continental land crab predators excludes J. planata from the continental mainland habitat, while the closely related Gecarcinus quadratus may have adaptations to high predation pressure.